Investigative Study on Potential Electrical Signals from Palm Trees in Gaza Strip - Hatem A Elaydi; Amal F Al-Astal; Aseel N Abed; Nora H Alaydi (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Abstract: This paper aims to analyze the electrical signals in a group of palm trees in the regions of Gaza City and Deir Albalah. It also investigates the stimuli of electrical potential (EP) in dates palm trees. It also explains factors such as: light, temperature, water level, tree age, sunset, direction, changing the reference, distance and proximity to the reference and electrode placement as stimuli on the EP of date palm trees. It assesses electrical signals (ESs) types in dates palm trees, generation and propagation of several ESs such action potential (AP), virtual potential (VP). The paper also demonstrates energy harvest potential, perspective applications and practical applications. The paper also provides a review summary of the effects of ESs on tipping, pruning, sunset, daybreak, photosynthesis, of lighting conditions, water availability.